Hubungan Pendidikan Ibu dengan Pemenuhan Minimum Dietary Diversity pada Anak Usia 6-23 Bulan: Tinjauan Naratif - Tiffania Khairunnisa Kurnia Abidin (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Undernutrition is a complex global issue that is still found in various parts of the world. To prevent the various impacts caused by undernutrition in children, early intervention is needed through the implementation of appropriate Infant and Young Child Feeding (IYCF) practices, one of which is meeting the Minimum Dietary Diversity (MDD) indicators for children aged 6-23 months. The fulfillment of MDD in children can be influenced by various factors, one of which is the maternal education. This narrative review aims to analyze the relationship between maternal education level and MDD fulfillment in children aged 6-23 months. A literature search was conducted for full-text open access articles published between 2015 and 2025 in English from scientific databases such as Scopus, PubMed, and ScienceDirect. Maternal education level has consistently been shown to be positively associated with MDD fulfillment in children aged 6-23 months across various countries, although the strength of the reported association varies depending on the social and economic context, and access to nutrition information and health services. Therefore, the implications of public health policies are important to be directed not only at improving long-term formal education, but also at short-term interventions through nutrition programs such as nutritional counseling related to complementary feeding in antenatal and postnatal services, posyandu, and community-based nutrition education.